Pengaturan Arsitektur Tanaman untuk Menyeimbangkan Sink dan Source serta Meningkatkan Pertumbuhan dan Hasil Kacang Koro Pedang - Abdullah Sarijan; Memen Surahman; Asep Setiawan; Giyanto Giyanto (Institut Pertanian Bogor, 2020)
The research to improve the growth, production, and seed quality of Jack Bean (Canavalia ensiformis L.) through pruning, which was carried out from May to October 2016 in Purwasari Village, Dramaga, Bogor Regency and continued by seed testing at the Seed Testing Laboratory, Bogor Agricultural University in December 2016. The research was designed in a randomized block design (RBD) with eight treatment of stem and branch pruning and one treatment without pruning as a control, i.e. without pruning of branches and stems (P1), pruning on the 10th stem nodes (P2 ), pruning on the 11th stem nodes (P3), pruning on the 5th branch nodes (P4), pruning on the five branch nodes and the 10th stem nodes (P5), pruning on the 5th branch nodes and stem nodes to -11 (P6), pruning on the 6th branch nodes (P7), pruning on the 6th branch nodes and 10th stem nodes (P8), and pruning on the 6th branch nodes and 11th stem nodes (P9). The results showed that pruning affected some of the results of the study, but was not able to increase the production of Jack Bean. Pruning treatment on the 5th branch nodes and 10th stem nodes (P5) produced the highest seed production (3.4 tons ha-1), the physical quality of the seeds produced was classified as moderate with a weight of 1000 seeds between 1273.3-1291.7 g. The physiological quality of the seed is moderate with maximum growth potential 84.0-90.7%, germination percentage 73.3-82.7%, germination speed 9.1-116.1% / etmal, germination uniformity 40.0-49 , 3% and vigor index of 14.0-20.0%. Keywords: germination rate, inflorescence, oas bakol, pod